Farmers survey of wild mammals species implicated in crop damage in the Okapi Wildlife Reserve (OWR-Epulu, Democratic Republic of the Congo): severity and control strategies - Nicaise D. Amundala; Pilipili Kasereka; Silvestre M. Gambalemoke; Jan Kennis; Charlotte Beneker; Alphonse M.-N. Maindo; Koto-te-Nyiwa Ngbolua; Akaibe M. Dudu; Pionus G.-B. Katuala (Nature Conservation Research: Заповедная наука, 2018)
Investigations on mammal species implicated in crop damage and control techniques used to protect fields was carried out in the Okapi Wildlife Reserve (OWR). The aim of this study was to identify mammal species causing damages on crops, the growth stages affected, the frequency and severity of damage in the fields and control techniques used. Data were collected in six villages using a standard questionnaire form translated in the main local languages (Swahili and Lingala), between 02–29 June and 07–31 August 2010. A probabilistic survey and structured interview have been used to collect data. Farmers of 7 main tribes were interviewed (a total of 210 farmers) who are living in OWR. The study shows that Primates (Cercocebus galeritus agilis, Papio anubis) and elephant (Loxodonta cyclotis) cause considerable damage during maturation and fructification of maize, cassava and bananas in the fields. Farmers keep their fields under guard to drive away animals and prevent crop damage.